Inhibition of cell-cell interactions in Myxococcus xanthus by congo red. - Arnold, J W (1988)
The function of molecules associated with the cell surface may be determined by examining the phenotype of cells treated with inhibitors specific to these cell surface molecules. This strategy was used to examine the function of the major Congo red receptor of the myxobacterium Myxococcus xanthus, which has a developmental cycle that involves social interactions among cells. A class of social motility mutations (A+ S-), known as dsp, may inhibit the same subcellular component as Congo red because the phenotype of wild-type cells which had been treated with Congo red resembled in several ways the phenotype of the Dsp mutants. First, Congo red inhibited agglutination of wild-type cells, whereas Dsp cells were incapable of agglutinating, even in the absence of Congo red. Second, Congo red inhibited fruiting body formation by wild-type cells and reduced the yield of myxospores. Untreated Dsp cells were unable to form fruiting bodies and produced few myxospores. Third, Congo red reduced the rate of wild-type gliding motility to a level comparable to that of untreated Dsp cells, but did not inhibit the A motility of Dsp cells. Finally, binding studies showed that Dsp cells lacked the major Congo red receptor. Wild-type cells bound Congo red with an apparent association constant of 2.4 X 10(5) M-1, while Dsp cells bound it with an apparent association constant of 8.5 X 10(3) M-1. Binding of Congo red to wild-type cells was saturated in less than 10 min and was reversible when excess Congo red was removed. These results suggest that the Congo red receptors are controlled by the S motility system and that these receptors are involved in cell cohesion, social motility, and fruiting body formation.